Parental knowledge, attitude, and behavioral factors in immunization response following a diphtheria outbreak in children in 2018-2019 - Nabila Arfimita; Edward Surjono (Indonesian Pediatric Society, 2020)
Background A diphtheria outbreak was declared at the end of 2017. The outbreak response immunization (ORI) was a key Indonesian government strategy to control diphtheria in three outbreak areas. This strategy was implemented starting December 11, 2018. Parents' positive knowledge, attitude, and behavior regarding diphtheria and the diphtheria ORI may influence the coverage of diphtheria ORI in Indonesia. Objective To assess for relationships between parental knowledge, attitude, and behavior to coverage of diphtheria ORI in children. Method This cross-sectional study was conducted at Kapuk Muara Public Elementary School 03, North Jakarta from November 2018 to August 2019. The respondents were parents of the schoolchildren. Parents filled questionnaires about their knowledge, attitude, and behavior with regards to diphtheria ORI coverage in children. Results The coverage of diphtheria ORI in children was 61.8%. From 110 respondents, 40.9% of parents had at least sufficient knowledge, 73.8% had good attitude, and 55.5% had good behavior regarding diphtheria and diphtheria ORI. Parental knowledge had no significant association to coverage of diphtheria ORI in their children. However, there were significant relationships between parental attitude and behavior to coverage of diphtheria ORI in their children. Conclusion The coverage of diphtheria ORI needs improvement. Most parents have sufficient level of knowledge, good attitude, and good behavior towards diphtheria and diphtheria ORI. There is no association between parental knowledge about diphtheria and diphtheria ORI to coverage of diphtheria ORI, but there are significant association of parental attitude and behavior toward diphtheria ORI coverage.